A Pilot Study on Crime Prevention Measures in Kočevje and Bela krajina: A Comparison Between the Roma and the Rest of the Local Population - Meško, Gorazd; Hacin, Rok (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
In this paper, we present the findings of a pilot study conducted in the spring of 2024, focusing on security in local communities in Kočevje and Bela krajina. The study emphasizes identifying the most effective crime prevention methods. Participants included Roma and other local residents from Kočevje, Črnomlje, Metlika, and Semič. Factor analysis revealed three key areas of preventive activities: social prevention, policing, and situational prevention. T-tests were conducted for all statements within these factors, showing statistically significant differences between the groups on all variables. This indicates that Roma and other residents perceive the meaning and importance of preventive activities differently. There is a need to balance these three preventive dimensions and to understand the measures already implemented and their extent. The results of the pilot study reflect the current discourse on Roma, social and security issues in the Dolenjska region.